2003
DOI: 10.1029/2002ja009796
|View full text |Cite
|
Sign up to set email alerts
|

AKR disappearance during magnetic storms

Abstract: [1] It is well known that auroral kilometric radiation (AKR) is intensified during substorms and has a good correlation with AE index. In the case of the magnetic storms, however, AKR characteristics have not been investigated. In this paper we report unexpected behavior of the storm-time AKR and its related particle precipitation: (1) AKR often disappears in the initial and main phases of the magnetic storms in spite of the large enhancement of AE index and field-aligned current; (2) At that time, the energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
10
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 27 publications
7
10
0
Order By: Relevance
“…A close relationship between AKR disappearances [ Morioka et al , 2003; Seki et al , 2005] and the electron density enhancements in and near the nightside auroral zone was demonstrated in the present study. In situ observations of the AKR source region above 3400 km altitude indicated that the electron densities in the AKR source region were of the order of 1 cm −3 or less [ Calvert , 1981; Perraut et al , 1990; Hilgers et al , 1991; Ergun et al , 1998].…”
Section: Discussionsupporting
confidence: 85%
“…A close relationship between AKR disappearances [ Morioka et al , 2003; Seki et al , 2005] and the electron density enhancements in and near the nightside auroral zone was demonstrated in the present study. In situ observations of the AKR source region above 3400 km altitude indicated that the electron densities in the AKR source region were of the order of 1 cm −3 or less [ Calvert , 1981; Perraut et al , 1990; Hilgers et al , 1991; Ergun et al , 1998].…”
Section: Discussionsupporting
confidence: 85%
“…Observing these amplitudes of squared wavelet coefficients, it can be concluded that the FACs are highly perturbed at high latitudes, where high‐frequency signals are dominant. This fact actually confirms the already known concept by Morioka et al []. They concluded that at higher latitudes high‐frequency signals play dominant role to characterize the penetration of charged particles and the energy injection phenomena, whereas at lower latitudes high‐frequency signal attenuates by coupling processes.…”
Section: Dwt Analysissupporting
confidence: 90%
“…This fact, actually, confirms the already known concepts that at higher latitudes the penetration of charged particles and the energy injection are characterized by phenomena that involve high-frequency signals; while at lower latitudes coupling processes do exist that attenuate high-frequency signals (Morioka et al 2003).…”
Section: Resultssupporting
confidence: 75%